How to measure anything : finding the value of intangibles in business / Douglas W. Hubbard - Hubbard, Douglas W., 1962- (John Wiley & Sons, Inc., 2014)
Now updated with new measurement methods and new examples, How to Measure Anything shows managers how to inform themselves in order to make less risky, more profitable business decisions This insightful and eloquent book will show you how to measure those things in your own business, government agency or other organization that, until now, you may have considered ""immeasurable, "" including customer satisfaction, organizational flexibility, technology risk, and technology ROI. Adds new measurement methods, showing how they can be applied to a variety of areas such as risk management and custom